2020
DOI: 10.3310/hsdr08420
|View full text |Cite
|
Sign up to set email alerts
|

The transition from children’s services to adult services for young people with attention deficit hyperactivity disorder: the CATCh-uS mixed-methods study

Abstract: Background Attention deficit hyperactivity disorder was previously seen as a childhood developmental disorder, so adult mental health services were not set up to support attention deficit hyperactivity disorder patients who became too old for child services. To our knowledge, this is the first in-depth study of the transition of attention deficit hyperactivity disorder patients from child to adult health services in the UK. Objectives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 139 publications
0
27
0
Order By: Relevance
“…1. A more detailed breakdown of the sample by data source and stakeholder identity is available in the CATCh-uS study report 20 Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1. A more detailed breakdown of the sample by data source and stakeholder identity is available in the CATCh-uS study report 20 Fig.…”
Section: Resultsmentioning
confidence: 99%
“…There is also scope for further mapping to explore the uptake and availability of shared care for ADHD, as qualitative research suggests that some young adults are treated exclusively by their GPs, while others experience difficulties finding a GP willing to prescribe medication even under shared care arrangements. 20 This suggests that the implementation of shared care arrangements may be highly variable.…”
Section: Discussionmentioning
confidence: 99%
“…Recruitment was continuously monitored to ensure that the sampling frame was being evenly populated. Potential young people and parent participants were identified by clinical research nurses at 10 NHS provider organizations (Trusts) 7 …”
Section: Methodsmentioning
confidence: 99%
“…This and low numbers of patients with ADHD who successfully transition to adult services in the UK 6 has focused attention on what can help support continuity of care. Existing studies have suggested parents are a key component for successful transition from child to adult services, with mothers typically taking responsibility for the transition process 7,8 . Based on earlier findings from our qualitative study exploring ADHD service transition in the UK, 7 in this study we present a typology of the roles and work parents of young people with ADHD adopt in the illness trajectory and how these change during transition to adulthood.…”
mentioning
confidence: 96%
“…A scoping review (Swift, Sayal, & Hollis, 2014) established many issues with transitional care, including a lack of appropriate adult care services. This review and more recent studies on transitional services (Janssens et al, 2020;Newlove-Delgado et al, 2018) also establishes that policy and guidelines recommendations are not often implemented into practice. NICE guidelines recommend that continued review of treatment should be shared between services (specialists' services and primary care).…”
Section: Adhd Pathway To Carementioning
confidence: 96%